Jewels of Kalispell : An Unexpected Grace - Book 3 - Peterson, Tracie; Woodhouse, Kimberley, 1973- (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2025)
"Actor Parker Bennett returns home to Kalispell after ten years and reunites with his first love, widowed Johanna St. John, who is juggling life as a mother and businesswoman. Just as Parker and Johanna believe they have a second chance at love, circumstances in both of their lives threaten any hope of a future together"--
Keywords: Actors -- Fiction; Widows -- Fiction; Millinery -- Fiction; Man-woman relationships -- Fiction; Kalispell (Mont.) -- Fiction; Montana -- Fiction; Christian fiction; Romance fiction; Novels